1993
DOI: 10.1088/0268-1242/8/5/024
|View full text |Cite
|
Sign up to set email alerts
|

Transparent conducting CdO films formed by chemical bath deposition

Abstract: The formation of transparent conducting CdO films by chemical bath deposition is reported for the first time. These films exhibit an optical transmittance and electrical conductivity much higher than those CdO films prepared by other physical vapour deposition techniques. They exhibit an optical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…The Cd(OH) 2 films were grown by the chemical bath technique on glass substrates [14], subsequently these films were immersed in a solution containing Te at 70 1C and with a pH in the interval 12-14. The preparation of solution containing Te represents a modification of procedure described by Sotelo et al [8].…”
Section: Methodsmentioning
confidence: 99%
“…The Cd(OH) 2 films were grown by the chemical bath technique on glass substrates [14], subsequently these films were immersed in a solution containing Te at 70 1C and with a pH in the interval 12-14. The preparation of solution containing Te represents a modification of procedure described by Sotelo et al [8].…”
Section: Methodsmentioning
confidence: 99%
“…The sol-gel process is generally used for the preparation of nanostructured films used in a variety of devices [19]. These characteristics make cadmium oxide a good candidate for solar cells, phototransistors, photodiodes, transparent electrodes and gas sensors [20,21]. This study focuses on the preparation and characterization of CdO produced by facile sol-gel spin coating and doped with copper at low proportions (2% and 3%).…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey confirmed that there are only few reports on the chemical synthesis (also known as chemical bath deposition, CBD) of CdO thin films [15]. Chemical bath deposition, which has been well known as prevalent low temperature aqueous method for directly depositing large-area thin films of semiconductors has advan-tages over above-mentioned techniques because it allows films to be deposited on nonplanar substrates that might not be chemically or mechanically stable at high temperatures [16].…”
Section: Introductionmentioning
confidence: 99%